Do We Stand Together? The Role of Perceived Personal and Group Threats in Predicting the Majority’s (Un)willingness to Confront Injustice on Behalf of a Minority - Celikkol, Göksu; Jasinskaja-Lahti, Inga; Renvik, Tuuli Anna; Vetik, Raivo; Sam, David Lackland (Frontiers in Psychology, 2021)
Purpose: By utilizing data from Estonia, Finland and Norway, this study explores how the perceptions of personal and group realistic threats, namely perceived ethnic discrimination and economic insecurity among national majorities, predict their unwillingness to confront injustice on behalf of Russian-speaking minority groups. Background: Previous research on collective action to promote minorities’ rights and social standing has focused either on minorities’ own action or factors promoting the willingness of majority group members to engage in collective action on behalf of minorities. In contrast, factors explaining the reluctance of majorities to engage in collective action on behalf of the minorities have remained less explored. For example, it is often ignored that majority members themselves may feel that they are not only threatened but also disadvantaged. Furthermore, the possible discrepancy between perceived personal vs. ingroup’s situation may influence their (un)willingness to confront injustice on behalf of the minority. Method: We employed polynomial regression with response surface analysis to analyze data gathered among national majority members in three countries (N=1341). Results: Perceived personal and group realistic threats were associated with heightened unwillingness to confront injustice on behalf of the Russian-speaking minority. Furthermore, participants were more unwilling to confront injustice when they perceived more group than personal threat. Conclusions: We found that majority group members’ (un)willingness to confront injustice on behalf of the minority is related to how secure they perceive their own and their group status. Our results contribute to previous research by pointing out the important drawbacks of majorities’ support for minorities’ wish for social change.